Exploring the Effects of bolA in Biofilm Formation and Current Generation by Shewanella oneidensis MR-1 - Silva, Ana V.; Edel, Miriam; Gescher, Johannes; Paquete, Catarina M. (Frontiers in Microbiology, 2020)
Microbial electrochemical technologies (METs) have emerged in recent years as a promising alternative green source of energy, with microbes consuming organic matter to produce energy or valuable byproducts. It is the ability of performing extracellular electron transfer that allows these microbes to exchange electrons with an electrode in these systems. The low levels of current achieved have been the limiting factor for the large-scale application of METs. Shewanella oneidensis MR-1 is one of the most studied electroactive organisms regarding extracellular electron transfer, and it has been shown that biofilm formation is a key factor for current generation. The transcription factor bolA has been identified as a central player in biofilm formation in other organisms, with its overexpression leading to increased biofilm. In this work we explore the effect of this gene in biofilm formation and current production by S. oneidensis MR-1. Our results demonstrate that an increased biofilm formation and consequent current generation was achieved by the overexpression of this gene. This information is crucial to optimize electroactive organisms towards their practical application in METs.